Pulse-frequency, high-intensity ion beams based on a vacuum arc; Soviet Physics Journal; Vol. 32, № 8 - Arzubov N. M. (1989, 1989)
The production and investigation of pulse-frequency, high-intensity ion beams based on a vacuum arc are examined. The influence of arc discharge parameters, accelerating voltage, residual gas pressure, pulse repetition rate, and geometric dimensions of the accelerator on the ion generation efficiency is analyzed